Experiences During a Psychoeducational Intervention Program Run in a Pediatric Ward: A Qualitative Study - Magalhães, Paula; Mourão, Rosa; Pereira, Raquel; Azevedo, Raquel; Pereira, Almerinda; Lopes, Madalena; Rosário, Pedro (Frontiers in Pediatrics, 2018)
Hospitalization, despite its duration, is likely to result in emotional, social, and academic costs to school-age children and adolescents. Developing adequate psychoeducational activities and assuring inpatients’ own class teachers’ collaboration, allows for the enhancement of their personal and emotional competences and the maintenance of a connection with school and academic life. These educational programs have been mainly designed for patients with long stays and/ or chronic conditions, in the format of Hospital Schools, and typically in Paediatric Hospitals. However, the negative effects of hospitalization can be felt in internments of any duration, and children hospitalized in smaller regional hospitals should have access to actions to maintain the connection with their daily life. Thus, this investigation aims to present a psychoeducational intervention program theoretically grounded within the self-regulated learning framework, implemented along one year in a paediatric ward of a regional hospital to all its school-aged inpatients, regardless of the duration of their stay. The program counts with two facets: the psychoeducational accompaniment and the linkage to school. All the 798 school-aged inpatients (Mage = 11.7; SDage = 3.71; Mhospital stay = 4 days) participated in pedagogical, leisure nature, and self-regulated learning activities designed to train transversal skills (e.g., goal-setting). Moreover, inpatients completed assigned study tasks resulting from the linkage between the students’ own class teachers and the hospital teacher. The experiences reported by parents/ caregivers and class teachers of the inpatients enrolling in the intervention allowed the researchers to reflect on the potential advantages of implementing a psychoeducational intervention to hospitalized children and adolescents that is: individually tailored, focused on leisure playful theoretically grounded activities that allow learning to naturally occur, and designed to facilitate school re-entry after hospital discharge. Parents/ caregivers highlighted that the program helped in the preparation for surgery and facilitated the hospitalization process, aided in the distraction from the health condition, promoted self-regulated learning competences, and facilitated the communication and linkage with school life. Class teachers emphasized the relevance of the program, particularly in the liaison between hospital and school, in the academic and psycho-emotional and leisure-educational support provided, and in smoothing the school re-entry.